Preparation method of ionic liquid modified material and sensor application process

By combining NiCo2O4 and γ-MnO2 composite nanomaterials with functionalized ionic liquids, a modified ionic liquid electrolyte solution was prepared, which solved the existing ammonia detection sensors in terms of conductivity, repeatability, response recovery speed and long-term stability. Inadequately, a significant improvement in sensor performance has been achieved.

CN119503903AActive Publication Date: 2025-02-25CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411687644.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing ammonia detection sensors have poor performance in terms of conductivity, repeatability, response recovery speed and long-term stability, and cannot meet the actual use needs.

Method used

Using a preparation method of ionic liquid modified materials, an ionic liquid electrolyte solution with improved performance is prepared by combining NiCo2O4 and γ-MnO2 composite nanomaterial with functionalized ionic liquid [HOETMIM][BF4] and applied it in ammonia detection sensor.

Benefits of technology

The conductivity, repeatability, response recovery speed and long-term stability of the ammonia detection sensor have been significantly improved, which has significantly improved the overall performance of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503903A_ABST
    Figure CN119503903A_ABST
Patent Text Reader

Abstract

The invention relates to the related technical field of ionic liquid, in particular to a preparation method of an ionic liquid modified material and a sensor application process, and the preparation method comprises the following steps: weighing a certain amount of NiCo2O4 and gamma-MnO2, and dissolving in deionized water; performing ultrasonic dispersion to obtain a mixed solution; transferring the obtained mixed solution into a stainless steel hydrothermal kettle lined with polytetrafluoroethylene, and carrying out a constant-temperature hydrothermal reaction; after the obtained substance is naturally cooled, centrifugally washing the substance; drying the obtained sample under a vacuum condition; and collecting the obtained solid substance, so as to obtain the NiCo2O4 / gamma-MnO2 composite nano material. The preparation method comprises the following steps: weighing a certain amount of [HOETMIM] [BF4] and NiCo2O4 / gamma-MnO2, and fully mixing by using a vortex mixer; performing ultrasonic treatment on the obtained mixture; the obtained sample is subjected to vacuum drying, and the NiCo2O4 / gamma-MnO2 composite material is obtained.By means of the designed modified material, the ionic liquid has better conductivity, repeatability, response recovery speed and long-term stability, and when the modified material is applied to the ammonia gas detection sensor, the overall performance of the ammonia gas detection sensor is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field related to ionic liquids, and in particular to a method for preparing an ionic liquid modified material and a sensor application process. Background Art

[0002] Ionic liquids are organic salts that are completely composed of anions and cations and are liquid at temperatures below 100°C. Ionic liquids have the characteristics of non-volatility, low vapor pressure, wide liquid range, high thermal stability, strong solubility, and adjustable structure and properties. In order to meet the needs of different reactions, specific functional groups are grafted onto the cation or anion structure of the ionic liquid to synthesize ionic liquids with unique properties, namely functionalized ionic liquids.

[0003] The existing ammonia detection sensors do not have good conductivity, repeatability, response recovery speed and long-term stability, which makes their overall performance poor and cannot meet the actual use requirements. Therefore, in view of the above situation, it is urgent to develop a preparation method of ionic liquid modified materials and sensor application process to overcome the shortcomings in current practical applications. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an ionic liquid modified material and a sensor application process to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing an ionic liquid modified material, the preparation method comprising the following steps: Step 1: Weigh a certain amount of NiCo2O4 and γ-MnO2 and dissolve them in deionized water; Step 2: Ultrasonic dispersion to obtain a mixed solution; Step 3, transferring the mixed solution obtained in step 2 to a stainless steel hydrothermal kettle lined with polytetrafluoroethylene to perform a constant temperature hydrothermal reaction; Step 4, after the material obtained in step 3 is cooled naturally, centrifuge and wash it several times; Step 5: drying the sample obtained in step 4 at 80°C under vacuum conditions for 12 hours; Step 6: Collect the solid material obtained in step 5 to obtain NiCo2O4 / γ-MnO2 composite nanomaterial; Step 7, weigh a certain amount of [HOETMIM][BF4] and NiCo2O4 / γ-MnO2, and mix them thoroughly using a vortex mixer; Step 8, subjecting the mixture obtained in step 7 to ultrasonic treatment; Step nine: vacuum dry the sample obtained in step eight at 60° C. for 12 hours to obtain a NiCo2O4 / γ-MnO2 composite material.

[0006] As a further solution of the present invention: in the step 1, the ratio of NiCo2O4 to γ-MnO2 is 1:1.

[0007] As a further solution of the present invention: the constant temperature hydrothermal reaction in step three is a hydrothermal reaction at a temperature of 120° C. for 24 hours.

[0008] As a further scheme of the present invention: In step one, the preparation method of NiCo2O4 is as follows: Ni(NO3)2·6H2O, Co(NO3)2·6H2O and polyvinylpyrrolidone PVP are dissolved in ethylene glycol and stirred for 30 minutes, the resulting solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, the autoclave is sealed and maintained at 180°C for 12 hours, then cooled to room temperature, the final product is collected by centrifugation, washed several times with water and ethanol, and then dried in an oven at 60°C for 12 hours, and finally the prepared precursor is calcined at 300°C for 2 hours.

[0009] As a further scheme of the present invention: In step 1, the preparation method of γ-MnO2 is as follows: MnSO4·H2O and (NH4)2S2O8 are dissolved in deionized water and stirred for 30 minutes, the resulting solution is transferred to a polytetrafluoroethylene-lined autoclave and maintained at 90°C for 24 hours, after cooling, separated by a centrifuge to obtain a black precipitate, which is washed three times with deionized water, and then the sample is dried at 80°C for 12 hours, and finally, calcined at 350°C in air for 4 hours.

[0010] As a further solution of the present invention: the ultrasonic treatment time in step 2 and step 8 is 30 minutes.

[0011] A process for applying an ionic liquid modified material in a sensor. The sensor consists of a shell, an electrode, blotting paper, a waterproof and breathable membrane, and a modified ionic liquid electrolyte solution. Before assembly, a working electrode is punched out from a dried polytetrafluoroethylene membrane using a manual press and a 17mm punch. The blotting paper is punched out using the same method, and a reference electrode and a counter electrode are cut out to assemble the sensor.

[0012] Compared with the prior art, the present invention has the following beneficial effects: The modified material designed in the present application enables the ionic liquid to have better conductivity, repeatability, response recovery speed and long-term stability. Applying it to the ammonia detection sensor significantly improves the overall performance of the ammonia detection sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is the output signal baseline diagram of the ammonia detection sensor based on the modified ionic liquid.

[0014] Figure 2 This is the repeatability test chart of the ammonia detection sensor based on the modified ionic liquid.

[0015] Figure 3 This is a test diagram of the response recovery of the ammonia detection sensor based on the modified ionic liquid.

[0016] Figure 4 This is a long-term stability test chart of the ammonia detection sensor based on modified ionic liquid.

[0017] Figure 5 This is the output signal baseline diagram of the ammonia detection sensor based on ILs / NiCo2O4 electrolyte.

[0018] Figure 6 This is the output signal baseline diagram of the ammonia detection sensor based on the electrolyte ILs / γ-MnO2.

[0019] Figure 7 This is the output signal baseline diagram of the ammonia detection sensor with ILs as the electrolyte.

[0020] Figure 8 Impedance spectra of ammonia sensors based on different electrolytes at 50 ppm NH3. DETAILED DESCRIPTION

[0021] The technical solution of the present application is further described in detail below in conjunction with specific implementation methods.

[0022] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0023] In one embodiment of the present invention, a method for preparing an ionic liquid modified material comprises the following steps: Step 1: Weigh 1.5 g of NiCo2O4 and 1.5 g of γ-MnO2 and dissolve them in 60 mL of deionized water; Step 2: Ultrasonic dispersion for 30 min to obtain a mixed solution; Step 3, transferring the mixed solution obtained in step 2 to a stainless steel hydrothermal kettle lined with polytetrafluoroethylene to perform a constant temperature hydrothermal reaction; Step 4, after the material obtained in step 3 is cooled naturally, centrifuge and wash it several times; Step 5: drying the sample obtained in step 4 at 80°C under vacuum conditions for 12 hours; Step 6: Collect the solid material obtained in step 5 to obtain NiCo2O4 / γ-MnO2 composite nanomaterial; Step 7, weigh 2.85 g [HOETMIM] [BF4] and 0.15 g NiCo2O4 / γ-MnO2, and mix thoroughly using a vortex mixer; Step 8, ultrasonically treating the mixture obtained in step 7 for 30 min; Step nine: vacuum dry the sample obtained in step eight at 60° C. for 12 hours to obtain a NiCo2O4 / γ-MnO2 composite material.

[0024] In one embodiment of the present invention, the constant temperature hydrothermal reaction in step three is a hydrothermal reaction at a temperature of 120° C. for 24 hours.

[0025] In one embodiment of the present invention, the preparation method of NiCo2O4 is as follows: 1.163 grams of Ni(NO3)2·6H2O, 2.328 grams of Co(NO3)2·6H2O and 0.0474 grams of polyvinylpyrrolidone PVP are dissolved in 80 ml of ethylene glycol and stirred for 30 minutes, and the resulting solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene. The autoclave is sealed and maintained at 180°C for 12 hours, then cooled to room temperature, and the final product is collected by centrifugation, washed several times with water and ethanol, and then dried in an oven at 60°C for 12 hours. Finally, the prepared precursor is calcined at 300°C for 2 hours.

[0026] In one embodiment of the present invention, the preparation method of γ-MnO2 is as follows: MnSO4·H2O (3.38 g, 20.0 mmol) and (NH4)2S2O8 (4.564 g, 20.0 mmol) are dissolved in 70 ml of deionized water and stirred for 30 min, the resulting solution is transferred to a polytetrafluoroethylene-lined autoclave (capacity of 100 ml) and kept at 90°C for 24 hours, after cooling, separated by a centrifuge to obtain a black precipitate, which is washed three times with deionized water, and then the sample is dried at 80°C for 12 hours, and finally, calcined at 350°C in air for 4 hours.

[0027] The principle of the ionic liquid electrochemical ammonia detection sensor is as follows: NH3 diffuses from the vent hole on the sensor cover through the waterproof breathable membrane to the surface of the working electrode, and is catalyzed by the working electrode catalyst layer to produce ammonium ions (NH 4+ ) and nitrogen (N2), NH 4+ Deprotonation generates ammonia and hydrogen ions (H+). The hydrogen ions and electrons flow through the electrolyte to the counter electrode, and a reduction reaction occurs on the electrode surface. The mechanism is as follows:

[0028] An application process of ionic liquid modified materials in sensors. The sensor consists of a housing, an electrode, a blotting paper, a waterproof breathable membrane and a modified ionic liquid electrolyte solution. Before assembly, a manual press and a 17mm punch are used to punch the working electrode off the dried polytetrafluoroethylene membrane. The blotting paper is punched out in the same way, and the reference electrode and the counter electrode are cut out. The sensor is assembled and tested for conductivity, repeatability, response recovery speed and long-term stability. The ammonia gas concentration used in the experiment is 200ppm. The aged sensor is connected to an electrochemical workstation, and ammonia is configured to a suitable concentration using a gas distribution device. The ammonia performance is then tested by the electrochemical workstation, and the test temperature is 25°C.

[0029] The test method is as follows: Real-time current measurement of 50 ppm ammonia concentration at room temperature for electrochemical ammonia sensors with different electrolytes.

[0030] 1. The electrolyte is [HOETMIM][BF4], its peak current is 6.2μA, its baseline is unstable, the response time is long, and the sensitivity does not meet the requirements.

[0031] 2. The electrolyte is [HOETMIM][BF4] doped with 5wt%, 10wt%, 15wt%, 20wt%, and 25wt% of γ-MnO2. The test results are as follows: the peak currents correspond to 6.2μA, 5.8μA, 1.9μA, 1.7μA, and 2μA, respectively. The sensitivity of 10wt% meets the requirements, and the response time is long.

[0032] 3. The electrolyte is [HOETMIM][BF4] doped with 5wt%, 10wt%, 15wt%, 20wt%, and 25wt% NiCo2O4. The test results are as follows: the peak currents correspond to 5μA, 4.7μA, 4.3μA, 3.9μA, and 3.8μA, respectively. The sensitivity of 5wt%, 10wt%, and 15wt% meets the requirements, but there is a problem of peak current drop.

[0033] 4. The electrolyte is [HOETMIM][BF4] doped with 5wt%, 10wt%, 15wt%, 20wt%, 25wt% NiCo2O4 / γ-MnO2 composite materials. The test results are as follows. The peak currents correspond to 4.56μA, 3.7μA, 5μA, 3μA, and 2.7μA, respectively. The sensitivities of 5wt% and 15wt% meet the requirements. After comparison, the response recovery time of 5wt% is better than that of 15wt%. The response time of 5wt% is 41s, the recovery time is 37s, and the sensitivity is 0.0912uA / ppm.

[0034] The electrolyte is [HOETMIM][BF4] doped with 5wt% NiCo2O4 / γ-MnO2 composite material, and the sensor performs real-time current measurement of ammonia concentrations from 0 to 100ppm at room temperature. When the sensor is exposed to concentrations of 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100ppm, the corresponding current values ​​are approximately 1.36uA, 2.34uA, 3.27uA, 4.32uA, 5.42uA, 6.32uA, 7.49uA, 8.61uA, 9.62uA and 10.5uA, respectively. Undoubtedly, as the ammonia concentration increases, the current value also increases. The function fitting of its current value Y and ammonia concentration X can be expressed as Y=0.13864+0.10435X, and the fitting correlation coefficient R 2 is 0.99921. This fitting result shows that the sensor response value has a good linear relationship with the ammonia concentration. The test results are shown in the figure: Combined with Figure 1 , Attachment Figure 5 , Attachment Figure 6 and attached Figure 7 It can be seen that the baseline of the output signal of the ammonia detection sensor based on the modified ionic liquid can be kept stable. Figure 2 It can be seen that the ammonia detection sensor based on the modified ionic liquid has excellent repeatability. Figure 3 It can be seen that the ammonia detection sensor based on the modified ionic liquid has a fast response recovery speed. Figure 4 It can be seen that the ammonia detection sensor based on the modified ionic liquid has excellent long-term stability. In summary, the modified material makes the ionic liquid have better conductivity, repeatability, response recovery speed and long-term stability. Applying it to the ammonia detection sensor has significantly improved the overall performance of the ammonia detection sensor.

[0035] Additionally, the impedance spectrum contains a straight line portion representing a diffusion-limited process and a semicircular portion (Rct) representing a charge-transfer-limited process. Figure 8 The Nyquist plots of Pt-Ru electrodes in different electrolytes are depicted, and the impedance of ILs / NiCo2O4 (curve c) is the largest due to the poor conductivity of NiCo2O4. For pure ILs (curve a), a well-defined semicircle with an Rct of 6.5Ω was found, revealing the obvious effect of interfacial resistance on electron transfer. As for ILs / γ-MnO2 (curve b), its impedance is greatly reduced due to the improved electron transfer efficiency of conductive ILs and γ-MnO2. In contrast, ILs / NiCo2O4 / γ-MnO2 (curve d) is almost a straight line with a very small Rct value. Therefore, it can be considered that the synergistic effect of the components in ILs / NiCo2O4 / γ-MnO2 promotes electron transfer.

[0036] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing an ionic liquid modified material, characterized in that: The preparation method comprises the following steps: Step 1: Weigh a certain amount of NiCo2O4 and γ-MnO2 and dissolve them in deionized water; Step 2: Ultrasonic dispersion to obtain a mixed solution; Step 3, transferring the mixed solution obtained in step 2 to a stainless steel hydrothermal kettle lined with polytetrafluoroethylene to perform a constant temperature hydrothermal reaction; Step 4, after the material obtained in step 3 is cooled naturally, centrifuge and wash it several times; Step 5: drying the sample obtained in step 4 at 80°C under vacuum conditions for 12 hours; Step 6: Collect the solid material obtained in step 5 to obtain NiCo2O4 / γ-MnO2 composite nanomaterial; Step 7, weigh a certain amount of [HOETMIM][BF4] and NiCo2O4 / γ-MnO2, and mix them thoroughly using a vortex mixer; Step 8, subjecting the mixture obtained in step 7 to ultrasonic treatment; Step nine: vacuum dry the sample obtained in step eight at 60° C. for 12 hours to obtain a NiCo2O4 / γ-MnO2 composite material.

2. The method for preparing the ionic liquid modified material according to claim 1, characterized in that: In the step 1, the ratio of NiCo2O4 to γ-MnO2 is 1:

1.

3. The method for preparing the ionic liquid modified material according to claim 2, characterized in that: The constant temperature hydrothermal reaction in step 3 is a hydrothermal reaction at a temperature of 120° C. for 24 hours.

4. The preparation method of the ionic liquid modified material and the sensor application process according to claim 1, characterized in that: In step 1, the preparation method of NiCo2O4 is as follows: Ni(NO3)2·6H2O, Co(NO3)2·6H2O and polyvinylpyrrolidone PVP are dissolved in ethylene glycol and stirred for 30 minutes, the resulting solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, the autoclave is sealed and maintained at 180°C for 12 hours, then cooled to room temperature, the final product is collected by centrifugation, washed several times with water and ethanol, and then dried in an oven at 60°C for 12 hours, and finally the prepared precursor is calcined at 300°C for 2 hours.

5. The preparation method of the ionic liquid modified material and the sensor application process according to claim 1, characterized in that: In step 1, the preparation method of γ-MnO2 is as follows: MnSO4·H2O and (NH4)2S2O8 are dissolved in deionized water and stirred for 30 minutes, the resulting solution is transferred to a polytetrafluoroethylene-lined autoclave and maintained at 90°C for 24 hours, after cooling, separated by a centrifuge to obtain a black precipitate, which is washed three times with deionized water, and then the sample is dried at 80°C for 12 hours, and finally, calcined at 350°C in air for 4 hours.

6. The preparation method of the ionic liquid modified material and the sensor application process according to claim 1, characterized in that: The ultrasonic treatment time in step 2 and step 8 is 30 minutes.

7. A process for applying the ionic liquid modified material in a sensor as claimed in claim 1, characterized in that: The sensor consists of a shell, electrodes, blotting paper, a waterproof and breathable membrane and a modified ionic liquid electrolyte solution. Before assembly, a manual press and a 17mm punch are used to punch out the working electrode from the dried polytetrafluoroethylene membrane. The same method is used to punch out the blotting paper, cut out the reference electrode and the counter electrode, and assemble the sensor.

Citation Information

Patent Citations

  • Method for preparing porous NiCo2O4 / MnO2 nuclear shell nanowire array supercapacitor electrode material

    CN103594253A

  • One-dimensional manganese dioxide@nickel cobaltate core-shell heterostructure composite as well as preparation method and application thereof

    CN106449176A

  • Method for preparing nanosheet nuclear shell structure

    CN106531449A

  • Alkali metal or alkali-ion batteries having high volumetric and gravimetric energy densities

    CN108292759A

  • Preparation method of spinel oxide nickel cobaltate

    CN115745024A